Adsorption Kinetic Models for Cr(Vi) onto Fruit Coir Pith of Nipa Palm - Nguyễn , Văn Sức; Nguyễn , Phan Thúy Hiền (Journal of Technical Education Science, 2010)
Batch experimental mode was used to study pseudo-kinetic models for adsorption of Cr (VI) by fruit coir pith of Nipa Palm. The obtained results confirmed that the adsorption process of Cr (VI) followed the pseudo-second kinetic model. From the linear relation between adsorption capacity and dose of adsorbent, the maximum adsorption capacity, qemax (mg/g) obtained to be of73 mg/g.